Magnetic Field-Enhanced Agglutination Readout Combined With Isothermal Reverse Transcription Recombinase Polymerase Amplification for Rapid and Sensitive Molecular Detection of Dengue Virus - Leon, Fanny; Pinchon, Elena; Mayran, Charly; Daynès, Aurélien; Morvan, François; Molès, Jean-Pierre; Cantaloube, Jean-François; Fournier-Wirth, Chantal (Frontiers in Chemistry, 2022)
Among the numerous molecular diagnostic methods, reverse transcription recombinase polymerase amplification (RT-RPA) is a simple, highly sensitive, and specific isothermal amplification method that avoids the use of expensive instruments. However, detection of amplified genomes often requires a fluorescence readout on costly readers or migration on a lateral flow strip with a subjective visual reading. To develop a new approach for the rapid and sensitive detection of viruses, we combined RT-RPA with a magnetic field-enhanced agglutination (MFEA) assay and assessed the ability of this method to detect the dengue virus (DENV). Magnetization cycles accelerated the capture of amplified DENV genomes between functionalized magnetic nanoparticles by a fast chaining process to less than 5 min; the agglutination was quantified by simple turbidimetry. This combined method was evaluated on 37 DENV RNA(+) and 30 DENV RNA(−) samples. The sensitivity and specificity were 89.19% (95% CI, 72.75%–100.00%) and 100% (95% CI, 81.74%–100.00%), respectively. This approach provides a solution for developing innovative diagnostic assays for the molecular detection of emerging infections.